Volume 4: Fluid Structure Interaction, Parts a and B 2006
DOI: 10.1115/pvp2006-icpvt-11-93239
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steam Generator Tube Bundle Vibrations on the Operating Diagram of a Nuclear Plant During Stretch Out

Abstract: During the normal cycle of a pressurized water reactor, boron concentration is reduced in the core until fuel burns up. A stretch out of the normal cycle is however possible afterwards, provided primary coolant temperature is reduced. In those stretch out periods, nuclear operators want to keep constant thermal power exchanged in the steam generator, in order to preserve its performances. Under that constraint, the required reduction in primary coolant temperature involves both a decrease of secondary cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…1). Several semi-empirical models have been proposed by Connors (1970), Blevins (1990), Price and Padoussis (1984), Lever and Weaver (1986), Granger and Padoussis (1996), Adobes and Gaudin (2004), Adobes et al (2006) relying on small perturbation development methods combined with empirical data enrichment. Each of these models takes into account a time delay between the solid response signal and the strain exerted by fluids on moving boundaries.…”
Section: Stability Analysismentioning
confidence: 99%
“…1). Several semi-empirical models have been proposed by Connors (1970), Blevins (1990), Price and Padoussis (1984), Lever and Weaver (1986), Granger and Padoussis (1996), Adobes and Gaudin (2004), Adobes et al (2006) relying on small perturbation development methods combined with empirical data enrichment. Each of these models takes into account a time delay between the solid response signal and the strain exerted by fluids on moving boundaries.…”
Section: Stability Analysismentioning
confidence: 99%
“…Indeed, the stability threshold respresents a design and operational limitation for many large scale heat exchangers and steam generators. For example, Adobes et al (1) demonstrated that the fluidelastic critical velocity is the limiting factor for power output in a nuclear steam generator during stretch out operation.…”
Section: Introductionmentioning
confidence: 99%